Field report form contributed by Robert W. Howe, spring 1983 - Howe, Robert W. (Robert William), 1952-et al (1983)
Spring report of birds contributed by Robert W. Howe. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed